The Girl in the Pandemic Transnational Perspectives - Smith, Ann; Mitchell, Claudia (Berghahn Books, 2023)
As seen in previous pandemics, girls and young women are particularly vulnerable as social issues such as homelessness, mental healthcare, access to education, and child labor are often exacerbated. The Girl in the Pandemic considers what academics, community activists, and those working in local, national, and global NGOs are learning about the lives of girls and young women during pandemics. Drawing from a range of responses during the pandemic including first person narratives, community ethnographies, and participatory action research, this collection offers a picture of how the COVID-19 pandemic played out in eight different countries.